2020
DOI: 10.1016/j.parepi.2020.e00172
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human cystic echinococcosis in South Kashmir, India

Abstract: Cystic echinococcosis is a zoonotic disease that causes economic losses and public health problems throughout the globe. Present study was undertaken to estimate the seroprevalence of cystic echinococcosis in humans of South Kashmir and to determine the risk factors associated with this disease. The present study was carried out from April 2017 to March 2018, during which 458 blood samples (from 222 males and 236 females) were collected from selected subjects from 12 villages of four districts along with demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
9
2
Order By: Relevance
“…Thus, the supply of Eg eggs for them occurs early in life and abundant (in the present study 79.5% of the cases and 100% of the cases with CEI cystic was in this conditions). The literature review shows studies with compatible results [16][17][18], but there are others that are not supporting our nding [20][21][22]. It is possible, that different cultural habits may explain these differences.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, the supply of Eg eggs for them occurs early in life and abundant (in the present study 79.5% of the cases and 100% of the cases with CEI cystic was in this conditions). The literature review shows studies with compatible results [16][17][18], but there are others that are not supporting our nding [20][21][22]. It is possible, that different cultural habits may explain these differences.…”
Section: Discussionmentioning
confidence: 52%
“…In the current study, the overall seropositivity of human CE was calculated as 21.5%. In comparison, the seroprevalence recorded in the Mediterranean basin region of Greece by Sotiraki et al (2003) [34] was higher at 29.00%, although Andrabi et al (2020) found a seroprevalence rate that was 4.4% lower than the present seropositivity rate in south Kashmir, India [4,8]. Further, Aklani et al (2014) [35] also recorded the seropositivity rate of 6.9% in four different towns of Denizli, Turkey.…”
Section: Discussionmentioning
confidence: 73%
“…The metacestode form, which is called the hydatid cyst, develops and causes CE in intermediate hosts such as livestock, and humans behave as accidental intermediate hosts [6]. Intermediate hosts (mostly ungulates and lagomorphs) are the primary reservoirs for human CE infection [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in India which is not far from Iran, the incidence varies from 1 to 200/100,000 in a year and most of the cases were from Kashmir, Andhra Pradesh, Tamil Nadu, and Central India [ 6 ].…”
Section: Discussionmentioning
confidence: 99%